The Adjustment of Crop Statistics: II - Willis, H. Parker (Journal of Political Economy, 1903)
discrepancy was found in the returns for every principal agri? cultural crop in the United States. It, moreover, has been pointed out that the student is apparently compelled to believe in the superior accuracy of the census figures as compared with those of the Department of Agriculture, unless satisfactory evidence going to discredit the work of the census office, and to throw unexpected shadows upon its methods, can ?>e produced. We have seen, too, that during the months immediately suc? ceeding the publication of the reports of the twelfth census, friends of the Agricultural Department sought to cast reflections upon the work of the census. That the Agricultural Department should feel annoyed at the errors in its statistics which seemed to be revealed with the